2020
DOI: 10.3390/bs10100158
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Academic Achievement with Cognitive Abilities: Cross-Sectional Study across School Education

Abstract: The relationship between cognitive abilities and academic achievement across schooling from the first to the eleventh grade was analyzed. Information processing speed, visuospatial working memory, number sense, and fluid intelligence were considered predictors of general academic achievement, which was derived from grades in mathematics, language, and biology. This cross-sectional study involved 1560 pupils who were in grades 1–11 at general education schools and were aged from 6.8 to 19.1 years (50.4% were bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 42 publications
1
37
0
2
Order By: Relevance
“…However, no significant associations were found with algorithmic arithmetic ( Fuchs et al 2006 ) and word problem-solving ( Lin 2020 ). A recent study found that information processing/decision speed, measured using the choice reaction time, is one of the key predictors of number sense, but it could not directly predict mathematical academic performance ( Tikhomirova et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, no significant associations were found with algorithmic arithmetic ( Fuchs et al 2006 ) and word problem-solving ( Lin 2020 ). A recent study found that information processing/decision speed, measured using the choice reaction time, is one of the key predictors of number sense, but it could not directly predict mathematical academic performance ( Tikhomirova et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analytical review conducted by Peng et al (2019) reported that fluid intelligence is moderately associated with reading skills and mathematics achievement. Tikhomirova et al (2020) also found that there is a significant link between nonverbal intelligence and academic achievement. The correlation levels with nonverbal intelligence were .48 for mathematics achievement, .47 for linguistic achievement, and .43 for biology achievement.…”
Section: Discussionmentioning
confidence: 84%
“…Gygi et al (2017) carried out a study with different intelligence tests as a result of which it was determined that the intelligence tests predict school grades at a significant level. Tikhomirova et al (2017) found a significant link between non-verbal intelligence test scores and achievement in mathematics. A meta-analytical review conducted by Peng et al (2019) reported that fluid intelligence is moderately associated with reading skills and mathematics achievement.…”
Section: Discussionmentioning
confidence: 87%
“…We used the proxy phenotype of academic achievement (EY) to represent past cognitive performance in the absence of a direct measure of processing speed. In support of this approach, a study using a sample of 1,560 pupils found that information processing speed is the key predictor of number sense, fluid intelligence and working memory, which in turn predict individual difference in academic achievement [67]. A further limitation is that processing speed as measured by RT is only one component of cognition and it may not be possible to extrapolate the results of this analysis to global cognitive resilience.…”
Section: Discussionmentioning
confidence: 99%